Reader Responses to Religion News: Discussions about Ark Encounter on Reddit - Sanders, W. Scott (Journal of religion, media and digital culture, 2020)
This study compares news reports about Ark Encounter, the young earth creationist theme park that opened in Kentucky in 2016, with contemporaneous posts on three Reddit communities to determine the strength of agenda setting by the news media for public discussions of controversial religious issues. Using topic modeling, this study compared the subjects covered in 139 discrete news articles with 2,926 comments in the subreddits of atheism, Christianity, and politics. The comparison found that many Reddit posts initially responded to news reports about controversies involving economics, politics, and beliefs. But online discussions proceeded to reflect diverse community interests more than the narrower focus of news reports. The atheism subreddit focused on issues of scientific evidence, the Christianity subreddit focused on hermeneutics of belief, and the politics subreddit focused on the separation of church and state. In short, the news media did not seem to exert a strong agenda-setting effect on discussions about Ark Encounter.